Numerical Investigation on Fe3O4-Water Nanofluid in the Presence of Magnetotactic Bacteria - Merve Gurbuz-Caldag; Bengisen Pekmen (Journal of applied and computational mechanics, 2025)
In this study, numerical research on natural convection nanofluid flow in the presence of magnetotactic bacteria and Fe3O4-water is performed. The time independent, dimensionless governing equations involving nanoparticle concentration and the number of microorganisms is numerically solved by global radial basis function method with two distinct boundary conditions in a square cavity including double diffusivity or not. Streamlines, isotherms, isolines of concentration and bacteria are illustrated for a range of parameters including Rayleigh number (102 ≤ Ra ≤ 105), bioconvection Rayleigh number (10 ≤ Rb ≤ 100), Peclet number (0.01 ≤ Pe ≤ 5), Lewis number (1 ≤ Le ≤ 10) and buoyancy ratio number (0.1 ≤ Nr ≤ 10). To inspect how various parameters affect heat and mass transport, the average Nusselt (Nu) and the average Sherwood (Sh) numbers on the heated wall are tallied. It is found that in the case of first boundary condition, heat transfer diminishes 11.4%, 24.9%, 39.7%, as Nr, Rb, Pe increases, and mass transfer rises 8.8%, 29.6% as Nr, Rb increases. On the other hand, Nu increases 6.13% and Sh decreases 26.8% as Le increments. In the case of second boundary condition, Nu and Sh rises with the augmentation of all physical parameters.